Global circulation of silver between Ming–Qing China and the Americas: Combining historical texts and scientific analyses. (3rd November 2020) - Sun, L.; Yang, G.; Liu, R.; Pollard, A. M.; Zhu, T.; Liu, C.
Abstract : The circulation of silver between the Americas, Europe and China has provided a critical impetus for modern globalization since the 16th century. Even though substantial documentary information about this process has been collected and processed, there is still an ongoing debate about its underlying mechanism and the nature of the economic model. This article argues that the scientific analyses of the silver bullion and coins of Ming–Qing China and the Americas can offer a new source of information about this issue. This pilot study shows that the Ag concentration in Ming and Qing silver bullion is higher than that of the Americas, by around 3% and 8%, respectively. In particular, Qing silver bullion made in different reigns shows a remarkably consistent Ag content. Such a difference in the fineness could further contribute to the colossal arbitrage noted by scholars for decades, resulting in high volumes of global trading fundamentally driven by the higher price of silver in China. While quantifying its exact economic and political impacts still appears a distant prospect, as the current database is rather sketchy and many intermediate processes remain unclear, integrating scientific analyses into historical research illustrates several new patterns which helps to rethink the global silver circulation in the early modern period.